Differences in exploitation and interference ability between two dominant ants: the invasive Argentine ant (Linepithema humile) and Tapinoma magnum. Issue 4 (4th July 2019) - Leonetti, Daniele; Centorame, Massimiliano; Fanfani, Alberto
Abstract : The Argentine ant is a highly invasive species that can cause significant ecosystem alterations. Its spread in the invaded areas is usually associated with the displacement of native ant species by means of strong interference competition mechanisms. According to recent studies, Tapinoma nigerrimum s.l., a native Mediterranean ant, can potentially limit the expansion of the Argentine ant. The aim of the present study is to determine the ethological features that discriminate against the ability of L. humile and T. magnum ( nigerrimum complex) to exploit a trophic resource both in the presence and in the absence of the competitor. We conducted behavioural assays on experimental colonies using foraging arenas in a laboratory experiment. Linepithema humile colonies showed the ethological profile typical of the species, as they carried out more intense recruitment, initially concentrated on the whole foraging site rather than on the bait. Linepithema humile workers were more aggressive and fought cooperatively during inter-specific interactions. Tapinoma magnum colonies apparently showed a more food-oriented profile as they were faster in the search for food and concentrated the recruitment on it rather than on the whole foraging site. Tapinoma magnum workers tried to avert the competitor using threat postures rather than physical aggression. Tapinoma magnum colonies were systematically excluded by L. humile colonies from the trophic resource and underwent a visible reduction in surface activity. These results suggest that L. humile used a different and more effective interference competition strategy compared to T. magnum .